Improving Teacher Performance Through Principal Leadership: A Literature Study in Palu City - Erlin Karmila; Harnida Wahyuni Adda; Niluh Putu Evvy Rossanty; Pricylia Chintya Dewi Buntuang (PT. Global World Scientific, 2024)
This study aims to explore the leadership role of school principals in improving teacher performance in Palu City through a literature study approach. In education, principals play a central role in creating a conducive working environment, encouraging professionalism and facilitating teachers' competency development. This study reviewed five scientific articles published between 2015 and 2024 and relevant to the topic of principal leadership in Palu City. The findings show that democratic leadership styles that encourage collaboration, teacher empowerment and persuasive communication have a positive influence on improving teacher performance. Furthermore, this study confirms that the success of school principals in managing human resources and implementing adaptive professional development programs determines the progress of education quality. The role of school principals is not only administrative but also strategic in facing the challenges of globalization, technological development and the competency-based curriculum. This study provides a practical contribution in formulating effective leadership strategies that support the improvement of education quality at the local level, particularly in Palu city. Therefore, collaboration between education stakeholders is key in strengthening the role of school principals as agents of change.